Analysis of the Impact of Fiscal and Exchange Rate on Growth: Lithuanian and Polish Case - Grainville, Philippe (Ekonomika, 2004)
The implementation of the EMU translates a new European policy mix. Our article proposes a study on the coordination of the monetary and budgetary policies for the Baltic States for their complete integration in the European policy mix. New members must ensure a monetary policy able to answer the objective of price stability; they take part in EMS II for three years. The budgetary sovereignty of governments is relative taking into account their obligations in accordance with the Pact of Stability and Growth. After the participation in the Monetary Union. the countries cannot change their exchange rate, they will loose weapon of the exchange rate and will have henceforth only the budgetary and fiscal policies to adjust their economies. These last are in addition limited by the criteria of convergence and the Pact of Stability and Growth. Credibility can be obtained only by affecting to each authority a specific objective, namely the price stability for the monetary authority and the soutenability of the national debt for the budgetary authority. A not balanced policy mix encourages financial turbulences, which occur when the investors have doubts as to the capacity of the country to absorb a shock (for example, in Russia). Budgetary deficit can reach a significant level. The monetary supply which can finance the deficit is then higher than the demand. According to monetarists, the budgetary discipline is associated with a partial control of prices and wages. In Poland, the “popiwek”, which is a tax on the increases in wages, attempts to reduce the budgetary deficit. Such a policy of freezed prices and wages is able to produce a fast deceleration of inflation. The public accounts thus tend to improve quickly. For monetarists, the monetary policy does not have any influence on the real sphere. The entry in the EMU supposes the loss of the exchange rate. The adjustment of the economic policy for the Member States in the event of asymmetrical shocks can be done only by the tax and budgetary policies. The latter are indirectly forced by the respect of the criteria of restoration of public finances; in the Central European East countries these problems are significant. In the current context of slowdown in economic activity, several governments of the Euro zone asked the European Central Bank to lower their rates to support the economic activity. Within this framework, we will study the impact on the growth of this new policy mix to which the Baltic States and Poland will be subjected.